Bilateral verses bilateral with tri-segmental endoscopic drainage using metal stents for high-grade malignant hilar biliary obstructions: A multicenter, randomized controlled trial: BRAVE study (BRAVE study). Issue 40 (7th October 2022) - Matsumoto, Kazuyuki; Mitsuhashi, Toshiharu; Kawamoto, Hirofumi; Ishida, Etsuji; Fujii, Masakuni; Akimoto, Yutaka; Seki, Hiroyuki; Ishihara, Yuki; Ogawa, Taiji; Yamazaki, Tatsuhiro; Fujii, Yuki; Kato, Hironari
Abstract : Introduction: Bilateral endoscopic drainage with self-expanding metallic stent (SEMS) can be used to manage hilar malignant biliary obstruction (HMBO) more effectively in comparison to unilateral drainage. An increased drainage area is predicted to prolong stent patency and patient survival. However, few reports have described the utility of trisegmental drainage and the benefits of using trisegmental drainage remain unknown. Thus, we launched a randomized clinical trial (RCT) to compare the clinical outcomes between bilateral and trisegmental drainage using SEMSs in patients with high-grade HMBO. Methods and analysis: This study was conducted as a multicenter randomized control trial (RCT) in 8 high-volume medical centers in Japan, and will prove the non-inferiority of bilateral drainage to trisegmental drainage. Patients with unresectable HMBO with Bismuth type IIIa or IV who pass the inclusion and exclusion criteria will be randomized to receive bilateral or trisegmental drainage at a 1:1 ratio. At each center, the on-site study investigators will obtain informed consent from the candidates, and will use an electronic data capture system (REDCap) to input necessary information, and register candidates with the registration secretariat. The primary endpoint is the rate of non-recurrent biliary obstruction (RBO) at 180 days after SEMSs placement. A −10% non-inferiority margin is assumed in the statistical analysis of the primary endpoint. Secondary endpoints include the rate of technical and clinical success, time to recurrent biliary obstruction (TRBO), causes of RBO, procedure-related adverse events (AEs), procedure time, TRBO with or without endoscopic sphincterotomy, overall survival, and the technical and clinical success rates at reintervention. Discussion: If the non-inferiority of bilateral drainage is demonstrated, it is predicted that the procedure time will be shortened and the medical cost will be reduced, which will be beneficial to the patient and the medical economy. Trial registration: Registered in Japan Registry of Clinical Trial-Registration (trial number. jRCTs062220038). This version number 1. Protocol dated Jun 23, 2022.